Ritual, Memory and Identity: Postcolonial Readings of Bukhara and Khorezm’s Cultural Continuity - Fayzulloyev, Otabek; Ochilov, Ulugbek; Kadirova, Zaynab; Rakhimov, Muzaffar; Djumayev, Akmal; Abulova, Zulfiya (Journal of Cultural Analysis and Social Change, 2025)
This paper looks at the relationship between ritual, memory and identity in the postcolonial geography of Bukhara and Khorezm, two historically important regions of Central Asia. Drawing on theoretical concepts from cultural memory studies, postcolonial theory and semiotics, this research pursues an understanding of how the commemorative and ritual practices function as mechanisms of cultural continuity in the face of colonial and Soviet transformations. Based on qualitative analysis of 50 scholarly sources, the study shows that these regions serve as outstanding cases of cultural resilience that are embodied in religious syncretism, adaptive hybridity and the strategic use of memory in identity formation. The results show that Bukhara and Khorezm are comparative microcosms of a postcolonial culture of cultural negotiation in which the pre-Islamic, Islamic and Soviet legacies combine to form distinctive modes of collective identity. This work makes a theoretical intervention in postcolonial Central Asian studies by bringing together Lotmanian semiotics and modern memory studies and illuminating areas of research deficits in terms of minority experiences and contemporary transformations.